Zinc oxide nanoparticles fabricated in the porous silica matrix by the sublimation method - Rudko, G.Yu.; Kovalenko, S.A.; Gule, E.G.; Bobyk, V.V.; Solomakha, V.M.; Bogoslovskaya, A.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The nanocomposite – nanoporous silica (SBA-16) containing ZnO quantum dots – was fabricated by the sublimation method. This novel route of synthesizing ZnO nanoparticles implies physical sorption of zinc acetylacetonate precursor into the matrix pores from the gaseous phase, hydrolysis of the precursor, and thermal decomposition of the product with formation of ZnO nanoclusters directly inside the pores. The nanocomposite was characterized by XRD, nitrogen adsorption-desorption isotherms, and photoluminescence spectroscopy methods. We observed the blue shift of the
ultraviolet luminescence of nanocomposite as compared to the luminescence of ZnO nanopowder as well as the decrease of the linewidth of the ultraviolet luminescence line, which points to the encapsulation of ZnO nanoparticles in the silica pores and narrowing of their size distribution.